Symbolic Meaning of Sere Bissu in Matompang Arajang Ceremony for Bugis Bone Community, South Sulawesi - Syahrianti Syam; Mahmud Tang; Safriadi Safriadi (Journal of Social Science, 2021)
Matompang Arajang ceremony is a traditional ceremony that is still passed down through generations and is still maintained until now by bugis bone people. Matompang Arajang is a ritual of cleaning bone royal heirlooms. Where the ceremony has a very important ritual that is Sere Bissu. So far, previous studies have not reached the level of finding the symbolic meaning of the Matompang Arajang ceremony. This article aims to describe the process or stages in the Matompang Arajang ceremony as well as explain the symbolic meaning of Sere Bissu in the Matompang Arajangceremony. The method used is descriptive-qualitative method with ethnographic approach. Data collection techniques in the form of observations, interviews and documentation. Data analysis is done with three stages, namely data restatement, data description and data interpretation. These three stages become the basis for drawing conclusions. Using anthropological theory, the author explains the culture and meaning used in the Sere Bissu ritual. The implementation of matompang arajang ceremony includes malekke toja, mapaota, memmang to rilangi, matompang and massossoro arajang. Sere Bissu ritual in mattompang arajang ceremony has symbolic meaning as a form of sacred communication to God as well as to the spirits of Bugis Bone ancestors who they believe still exist around their lives.